Risk and protective factors for mental ill-health in elite para- and non-para athletes - Olive, Lisa S.; Rice, Simon M.; Gao, Caroline; Pilkington, Vita; Walton, Courtney C.; Butterworth, Matt; Abbott, Lyndel; Cross, Gemma; Clements, Matti; Purcell, Rosemary (Frontiers in Psychology, 2022)
Objective: To apply a socioecological approach to identify risk and protective factors across levels of the ‘sports-ecosystem’, which are associated with mental health outcomes among athletes in para-sports and non-para sports. A further aim is to determine whether para athletes have unique risks and protective factor profiles compared to non-para athletes. Methods: A cross-sectional, anonymous online-survey was provided to all categorised (e.g., highest level) athletes aged 16 years and older, registered with the Australian Institute of Sport. Mental health outcomes included mental health symptoms (GHQ-28), general psychological distress (K-10), risky alcohol consumption (AUDIT-C) and eating disorder risk (BEDA-Q). Risk and protective factors across multiple levels of the socioecological model, including individual, microsystem, exosystem and macrosystem level factors were assessed via self-report. Results: 427 elite athletes (71 para and 356 non-para athletes) participated in the study. No significant differences in the rates of mental health problems were observed between para and non-para athletes. Both differences and similarities in risk and protective factor profiles were found across the multiple levels of the sports-ecosystem. Weak evidence was also found to support the hypothesis that certain risk factors, including experiencing two or more adverse life events in the past year, sports related concussion, high self-stigma, inadequate social support and low psychological safety conferred a greater risk for poorer mental health outcomes for para athletes in particular. Conclusion: Risk factors occurring across various levels of the sports ecosystem, including individual, interpersonal and organisational level risk factors were found to be associated with a range of poorer mental health outcomes. The association between mental ill-health and certain risk factors, particularly those at the individual and microsystem level, appear to be greater for para athletes. These findings have important implications for policy and mental health service provision in elite sports settings, highlighting the need for more nuanced approaches to subpopulations, and the delivery of mental health interventions across all levels of the sports ecosystem.